Evaluation of Commonly Used Temporary Skin Dressings and a Newly Developed Collagen Matrix for Treatment of Superficial Wounds. (December 2015) - Held, Manuel; Rothenberger, Jens; Engelke, Anne-Sophie; Tolzmann, Dascha Sophie; Esfahani, Babak Janghorban; Schaller, Hans-Eberhard; Rahmanian-Schwarz, Afshin
ABSTRACT: OBJECTIVE: In the authors' experience, extended superficial-thickness wounds often were treated with the application of synthetic temporary wound dressings. There is a broad range of expensive products available in this market. The aim of this study was to compare commonly used temporary skin dressings with a newly developed collagen matrix. METHODS: A total of 56 standardized superficial skin defects were generated on the back of 28 adult male Lewis rats using a skin dermatome. The wounds were treated with Biobrane (Smith & Nephew, St Petersburg, Florida) (n = 14), Suprathel (PolyMedics, Denkendorf, Germany) (n = 14), and newly developed Collagen Cell Carrier (Naturin Viscofan, Weinheim, Germany) (CCC; n = 14). Histological evaluation was performed at 3 months' postoperative in regard to quality of newly formed skin. RESULTS: In regard to epidermal cell count and thickness of skin, Biobrane and Suprathel demonstrated comparable values, whereas CCC demonstrated higher epidermal cell count and thicker neoepidermis. The epidermal thickness of CCC was comparable to untreated, healthy skin. CONCLUSIONS: The presented results reveal the potential of CCC in the treatment of superficial skin defects and encourages further evaluation of CCC in surgical applications and regenerative medicine.